Iris cyst after cataract extraction: A case report - Hartana & Suhardjo, Hartana & Suhardjo (Universitas Gadjah Mada, 1992)
A case of 50 years-old woman with iris cyst 214 years after cataract extraction has been reported. Removal of the cyst had been performed, but a vitreocorneal adherence appeared. This was a complication of cystectomic procedure and caused a progression of corneal edema and a bullous keratopathy, so that the prognosis remained poor.Iris cyst is the most malignant complication of cataract extraction. Estimates of the incidence vary from 0.00 to 0.11%. The history of illness, clinical signs and biomicroscopic examination suggested that the case was an epithelial invasion into the anterior chamber following cataract extraction.Key Words: iris cyst - cystectomy - vitreocorneal adherence - bullous keratopathy - cataract